2020
DOI: 10.1074/jbc.ra120.012974
|View full text |Cite
|
Sign up to set email alerts
|

Secretory galectin-3 induced by glucocorticoid stress triggers stemness exhaustion of hepatic progenitor cells

Abstract: Adult progenitor cell populations typically exist in a quiescent state within a controlled niche environment. However, various stresses or forms of damage can disrupt this state, which often leads to dysfunction and aging. We built a glucocorticoids (GC) induced liver damage model of mice, found that GC stress induced liver damage, leading to consequences for progenitor cells expansion. However, the mechanisms by which niche factors cause progenitor cells proliferation are largely unknown. We demonstrate that,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
2
4
0
Order By: Relevance
“…In contrast to quiescent, apoptotic, or terminally differentiated cells, senescent cells have incurred an irreversible cell cycle arrest, yet remain viable, have alterations in metabolic activity and undergo dramatic changes in gene expression 38 . In support of our hypothesis, a previous study of liver progenitor cells reported that GC exposure induced cell proliferation leading to long-term replicative senescence/stemness exhaustion 39 , and GC is also reported to induce senescence of NSPCs (neural stem/progenitor cells) in vitro 40 . The presence of senescent cells in the proliferative zone of the GC-exposed hypothalamus at 13 dpf might explain why we observed reduced expression of pcna and rx3 , and a reduced proliferative capacity of the remaining glial cells in the proliferative zone of star:bPAC+ larvae.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast to quiescent, apoptotic, or terminally differentiated cells, senescent cells have incurred an irreversible cell cycle arrest, yet remain viable, have alterations in metabolic activity and undergo dramatic changes in gene expression 38 . In support of our hypothesis, a previous study of liver progenitor cells reported that GC exposure induced cell proliferation leading to long-term replicative senescence/stemness exhaustion 39 , and GC is also reported to induce senescence of NSPCs (neural stem/progenitor cells) in vitro 40 . The presence of senescent cells in the proliferative zone of the GC-exposed hypothalamus at 13 dpf might explain why we observed reduced expression of pcna and rx3 , and a reduced proliferative capacity of the remaining glial cells in the proliferative zone of star:bPAC+ larvae.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies showed that the proliferation ability of cancer cells was significantly reduced after knockdown of Gal-3 in various cancer types ( Lalancette-Hebert et al, 2012 ; Ajani et al, 2018 ; Yang et al, 2020 ). Our data also demonstrated that inhibition of Gal-3 dramatically suppressed the proliferation and differentiation ability of ICC HCCC9810 cells as evidenced by increased cell ploidy time.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been clearly shown that 15 days of dexamethasone treatment causes many cardiovascular abnormalities, such as increased blood pressure, cardiac fibrosis, and cardiomyocyte apoptosis. [41] Besides, in a recent study, Yang et al [58] showed that 10-day of dexamethasone treatment (25 mg/kg per day) resulted in significantly increased blood glucose and decreased liver weight. Gal-3 gene expression in mice liver was also increased compared to the control group.…”
Section: Glucocorticoids and Gal-3 In Cardiomyocytementioning
confidence: 99%